2005
DOI: 10.1029/2004ja010856
|View full text |Cite
|
Sign up to set email alerts
|

Thermosphere density variations due to the 15–24 April 2002 solar events from CHAMP/STAR accelerometer measurements

Abstract: [1] Thermosphere densities near 410 km altitude between ±87°latitude and near 0430 and 1530 local time from the accelerometer experiment on the CHAMP satellite are used to elucidate the response to three coronal mass ejections occurring on 17, 19, and 21 April 2002. Comparisons of the global responses with the NRLMSISE00 empirical model and the NCAR TIEGCM are performed and interpreted. An enhanced daytime response in comparison to TIEGCM on 17 April is found that is suggestive of preconditioning of the atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 30 publications
4
72
1
Order By: Relevance
“…The large scale spatial variations in the density, mostly related to altitude/latitude variations are captured by the first singular vector; time variations are captured by the associated projection coefficient, down to time scale on the order of one orbital period. Smaller scale spatial and time variations typically correspond to the variations induced by gravity waves generated by Joule heating as the one discussed by Forbes et al (2006) and Bruinsma et al (2006). Their morphology along each orbit segment is captured by the residual, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The large scale spatial variations in the density, mostly related to altitude/latitude variations are captured by the first singular vector; time variations are captured by the associated projection coefficient, down to time scale on the order of one orbital period. Smaller scale spatial and time variations typically correspond to the variations induced by gravity waves generated by Joule heating as the one discussed by Forbes et al (2006) and Bruinsma et al (2006). Their morphology along each orbit segment is captured by the residual, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In this latitude range, this error may reach 10% during large storms, which is small compared to the 200% or larger observed density enhancements during such large magnetic storms (Sutton et al, 2005;Forbes et al, 2006;Bruinsma et al, 2006).…”
Section: Svd Analysis Of Champ Densities During May 2003mentioning
confidence: 99%
See 2 more Smart Citations
“…The statistical nature of MSIS dictates that accurate predictions hold only during quiet and steady state conditions. Several studies have shown that significant differences exist between in situ measurements and MSIS-modeled thermospheric mass densities during geomagnetic disturbances [e.g., Bruinsma et al, 2006;Burke et al, 2007;Forbes et al, 2005]. The severity of underestimation by MSIS can range from a factor 2 [e.g., Sutton et al, 2005] up to as much as 5 when expressed in terms of the enhancement above the prestorm densities [Liu and Lühr, 2005].…”
Section: Introductionmentioning
confidence: 99%